Drug eruptions: An 8-year study including 106 inpatients at a dermatology clinic in Turkey - Fatma Akpinar; Emine Dervis (Wolters Kluwer Medknow Publications, 2012)
Background: Few clinical studies are found in the literature about patients hospitalized with a diagnosis of cutaneous drug eruption. Aims: To determine the clinical types of drug eruptions and their causative agents in a hospital-based population. Materials and Methods: This retrospective study was performed in the Dermatology Department of Haseki General Hospital. Through 1751 patients hospitalized in this department between 2002 and 2009, inpatients diagnosed as drug eruption were evaluated according to WHO causality definitions. 106 patients composed of probable and possible cases of cutaneous drug eruptions were included in this study. Results: Seventy one females and 35 males were evolved. Mean age was 44.03±15.14. Duration between drug intake and onset of reaction varied from 5 minutes to 3 months. The most common clinical type was urticaria and/or angioedema in 48.1% of the patients, followed by maculopapular rash in 13.2%, and drug rash with eosinophilia and systemic symptoms in 8.5%. Drugs most frequently associated with cutaneous drug eruptions were antimicrobial agents in 40.5% of the patients, followed by antipyretic/anti-inflammatory analgesics in 31.1%, and antiepileptics in 11.3%. Conclusion: Urticaria and/or angioedema and maculopapular rash comprised majority of the drug eruptions. Rare reactions such as acute generalized exanthematous pustulosis, sweet syndrome, oral ulceration were also found. Antimicrobial agents and antipyretic/anti-inflammatory analgesics were the most commonly implicated drugs. Infrequently reported adverse reactions to myorelaxant agents, newer cephalosporins and fluoroquinolones were also detected. We suppose that studies on drug eruptions should continue, because the pattern of consumption of drugs is changing in every country at different periods and many new drugs are introduced on the market continuously.